DNA–DNA hybridization study of strains of Chryseobacterium, Elizabethkingia and Empedobacter and of other usually indole-producing non-fermenters of CDC groups IIc, IIe, IIh and IIi, mostly from human clinical sources, and proposals of Chryseobacterium bernardetii sp. nov., Chryseobacterium carnis sp. nov., Chryseobacterium lactis sp. nov., Chryseobacterium nakagawai sp. nov. and Chryseobacterium taklimakanense comb. nov - Holmes, B. (Int J Syst Evol Microbiol, 2013)
The taxonomic classification of 182 phenotypically similar isolates was evaluated using DNA–DNA hybridization and 16S rRNA gene sequence analysis. These bacterial isolates were mainly derived from clinical sources; all were Gram-negative non-fermenters and most were indoleproducing. Phenotypically, they resembled species from the genera Chryseobacterium, Elizabethkingia or Empedobacter or belonged to CDC groups IIc, IIe, IIh and IIi. Based on these analyses, four novel species are described: Chryseobacterium bernardetii sp. nov. (type strain NCTC 13530(T)=CCUG 60564(T)=CDC G229(T)), Chryseobacterium carnis sp. nov. (type strain NCTC 13525(T)=CCUG 60559(T)=CDC G81(T)), Chryseobacterium lactis sp. nov. (type strain NCTC 11390(T)=CCUG 60566(T)=CDC KC1864(T)) and Chryseobacterium nakagawai sp. nov. (type strain NCTC 13529(T)=CCUG 60563(T)=CDC G41(T)). The new combination Chryseobacterium taklimakanense comb. nov. (type strain NCTC 13490(T)=X-65(T)=CCTCC AB 208154(T)=NRRL B-51322(T)) is also proposed to accommodate the reclassified Planobacterium taklimakanense.